Mobile robot construction for edutainment application - Ribeiro, A. Fernando (2007)
As time goes on, there are more and more robotics applications. The limit is almost the imagination of each person. A great deal of industrial work can yet be done by robots and new ideas are blossoming. The entertainment industry is arriving and there are already many ideas as well as real robots on the field. It is important to point out that the entertainment applications not just entertain people as it also brings new research which will then be used in industrial work applications. This paper describes a team of robot football players which compete in a worldwide scientific challenge – the RoboCup.